Influenza vaccine effectiveness among patients with high-risk medical conditions in the United States, 2012–2016. Issue 52 (18th December 2018) - Shang, Mei; Chung, Jessie R.; Jackson, Michael L.; Jackson, Lisa A.; Monto, Arnold S.; Martin, Emily T.; Belongia, Edward A.; McLean, Huong Q.; Gaglani, Manjusha; Murthy, Kempapura; Zimmerman, Richard K.; Nowalk, Mary Patricia; et al.
Highlights: We analyzed influenza VE among outpatients by high risk condition, age, and flu type during in U.S. VE among patients with high risk conditions are approaching the levels as it among patients without. VE among children and adults with high risk wasn't different from it among those without. VEs against flu A(H3N2), (H1N1)pdm09, and B were similar in patients with and without high-risk. Abstract: Background: Annual influenza vaccination has been recommended for persons with high-risk conditions since the 1960s. However, few estimates of influenza vaccine effectiveness (VE) for persons with high-risk conditions are available. Methods: Data from the U.S. Influenza Vaccine Effectiveness Network from 2012 to 2016 were analyzed to compare VE of standard-dose inactivated vaccines against medically-attended influenza among patients aged ≥6 months with and without high-risk medical conditions. Patients with acute respiratory illness were tested for influenza by RT-PCR. Presence of high-risk conditions and vaccination status were obtained from medical records. VE by influenza virus type/subtype and age group was calculated for patients with and without high-risk conditions using the test-negative design. Interaction terms were used to test for differences in VE by high-risk conditions. Results: Overall, 9643 (38%) of 25, 369 patients enrolled during four influenza seasons had high-risk conditions; 2213 (23%) tested positive for influenza infection. For all ages, VE against any influenza was lower among patients with high-risk conditions (41%, 95% CI: 35–47%) than those without (48%, 95% CI: 43–52%; P-for-interaction = 0.02). For children aged <18 years, VE against any influenza was 51% (95% CI: 39–61%) and 52% (95% CI: 39–61%) among those with and without high-risk conditions, respectively ( P-for-interaction = 0.54). For adults aged ≥18 years, VE against any influenza was 38% (95% CI: 30–45%) and 44% (95% CI: 38–50%) among those with and without high-risk conditions, respectively ( P-for-interaction = 0.21). For both children aged <18 and adults aged ≥18 years, VEs against illness related to influenza A(H3N2), A(H1N1)pdm09, and influenza B virus infection were similar among those with and without high-risk conditions. Conclusions: Influenza vaccination provided protection against medically-attended influenza among patients with high-risk conditions, at levels approaching those observed among patients without high-risk conditions. Results from our analysis support recommendations of annual vaccination for patients with high-risk conditions.